A new method of ergonomic testing of gloves protecting against cuts and stabs during knife use. (May 2017) - Irzmańska, Emilia; Tokarski, Tomasz
Abstract: The paper presents a new method of ergonomic evaluation of gloves protecting against cuts and stabs during knife use, consisting of five manual dexterity tests. Two of them were selected based on the available literature and relevant safety standards, and three were developed by the authors. All of the tests were designed to simulate occupational tasks associated with meat processing as performed by the gloved hand in actual workplaces. The tests involved the three most common types of protective gloves (knitted gloves made of a coverspun yarn, metal mesh gloves, and metal mesh gloves with an ergonomic polyurethane tightener) and were conducted on a group of 20 males. The loading on the muscles of the upper limb (adductor pollicis, flexor carpi ulnaris, flexor carpi radialis, and biceps brachii) was measured using surface electromyography. For the obtained muscle activity values, correlations were found between the glove type and loading of the upper limb. ANOVA showed that the activity of all muscles differed significantly between the five tests. A relationship between glove types and electromyographic results was confirmed at a significance level of α = 0.05. Highlights: New approach to study of ergonomic gloves protecting from cuts and stabs by hand knives was presented. Dexterity tests simulating manual tasks are useful tool for evaluation ergonomic properties of protective gloves. Selection of an appropriate test enables detection of objective differences, confirmed by changes in EMG signal.